PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PLN (PERSERO) PEMATANGSIANTAR - Nainggolan, Grace Agustina Arthauli; Calen, Calen; Sinaga, Novendra Adisaputra (Politeknik Bisnis Indonesia, 2025)
Abstract The performance of an employee towards the company is very important in the world of work, every company wants its employees to have good performance in working, for that, to create good performance among employees, a good work environment and organizational culture and job satisfaction are needed. This study aims to determine and analyze the influence of the work environment and organizational culture through job satisfaction as an intervening variable that has a positive and significant effect on employee performance at PT. PLN (Persero) Pematangsiantar. The type of research used by the researcher is quantitative descriptive. The population used in this study were all employees of PT. PLN (Persero) Pematangsiantar totaling 55 people who work in all divisions within the company. Data analysis techniques were carried out using path analysis. The results of the study showed that the work environment had a positive and significant effect on employee performance, organizational culture had a positive and significant effect on employee performance, the work environment and organizational culture had a positive and significant effect on employee job satisfaction. Job satisfaction can mediate between work environment and organizational culture on employee performance at PT. PLN (Persero) Pematangsiantar, Data processing using SPSS 22 application. Keywords: Work environment, organizational culture, Job Satisfaction, and Employee Performance